2021
DOI: 10.1002/dev.22213
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and autonomic stress systems activity in young adults raised by mothers with mental health and substance abuse problems: A prospective cohort study

Abstract: Among the well-known physiological consequences of early adverse environments is dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis. A number of studies demonstrate that negative parenting and living with parents with a history of substance abuse and mental health problems may be associated with HPA axis dysregulation in children. In contrast, studies of more delayed effects in adult offspring, especially prospective, are still scarce. This study was a prospective longitudinal investigation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…In humans, a close relationship has been found among cognitive abilities (Kaplan et al, 2001;Nelson III et al, 2007), physical health (Burenkova et al, 2021;Poulton et al, 2002;Wickrama et al, 2005), and mental health (Kessler et al, 2010;Mullen et al, 1996;Poulton et al, 2002;Wickrama et al, 2005) on one hand and adverse early-life conditions on the other. In particular, dysfunctional family environment in childhood (physical and sexual abuse, psychological pressure, lack of parental care, divorce, or death of parents) is often associated with the emergence of psychopathology 2 (depression, alcohol, and drug addiction, post-traumatic stress disorder, bipolar disorder, among others) (LeMoult et al, 2020;McKay et al, 2022;Trotta et al, 2015) and 2 However, a nonlinear U-shaped relationship was also demonstrated between exposure to early-life adversity and subsequent resilience and improved mental health, indicating that individuals with some lifetime adversity reported better outcomes than those with a high level of adversity or no history of adversity (Collins et al, 2023;Seery et al, 2010).…”
Section: Maternal Care and Development Of Behavioral And Physiologica...mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, a close relationship has been found among cognitive abilities (Kaplan et al, 2001;Nelson III et al, 2007), physical health (Burenkova et al, 2021;Poulton et al, 2002;Wickrama et al, 2005), and mental health (Kessler et al, 2010;Mullen et al, 1996;Poulton et al, 2002;Wickrama et al, 2005) on one hand and adverse early-life conditions on the other. In particular, dysfunctional family environment in childhood (physical and sexual abuse, psychological pressure, lack of parental care, divorce, or death of parents) is often associated with the emergence of psychopathology 2 (depression, alcohol, and drug addiction, post-traumatic stress disorder, bipolar disorder, among others) (LeMoult et al, 2020;McKay et al, 2022;Trotta et al, 2015) and 2 However, a nonlinear U-shaped relationship was also demonstrated between exposure to early-life adversity and subsequent resilience and improved mental health, indicating that individuals with some lifetime adversity reported better outcomes than those with a high level of adversity or no history of adversity (Collins et al, 2023;Seery et al, 2010).…”
Section: Maternal Care and Development Of Behavioral And Physiologica...mentioning
confidence: 99%
“…In line with the biological embedding theory, early‐life experiences have the potential to induce enduring physiological and molecular alterations that become embedded in the biological systems, impacting outcomes like health, well‐being, and behavior across the lifespan (Hertzman, 2012). In studies on humans, the close relationship of adverse early‐life conditions, mainly associated with the quality of parental care, with cognitive abilities (Kaplan et al., 2001; Nelson III et al., 2007), physical health (Burenkova et al., 2021; Poulton et al., 2002; Wickrama et al., 2005), and mental health (Kessler et al., 2010; Mullen et al., 1996; Poulton et al., 2002; Wickrama et al., 2005) of adults has been revealed in empirical studies and further confirmed by multiple meta‐analyses on cognitive abilities (Goodman et al., 2019), physical (Jakubowski et al., 2018), and mental health outcomes (LeMoult et al., 2020; McKay et al., 2022; Trotta et al., 2015). In experiments with laboratory animals, effects of early‐life adversity (ELA), again related to the quality of parental care, on the future physiological (Champagne et al., 2003; Francis et al., 2002) and behavioral (Champagne et al., 2003, 2008; Francis et al., 1999, 2002; Franklin et al., 2010) phenotypes were revealed in multiple rodent models, such as maternal deprivation (MD) or separation, variation in the level of maternal care, limited bedding and nesting (LBN), and others (Bonapersona et al., 2019; Duque‐Quintero et al., 2022; Rocha et al., 2021) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%